Phytochemical and antifungal screening of Acalypha wilkesiana Mull Arg (Euphorbiaceae) leaf extract in cream formulations - Isaac, Aremu Olusola; Tolulope, Adekoya Christiana (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
The plant Acalypha wilkesiana (Euphorbiaceae) has been ethnomedicinally reported to have antifungal activities. There is the need to have convenient dosage formulations that would be therapeutically useful to patients .The present study seeks to screen for the presence of secondary metabolites present in the plant and then evaluate the extract and cream formulations against certain selected fungal organisms. The extract was obtained from pulverized dried leaves with ethanol 95%v/v at powdered leaves to solvent ratio 1:10.The plant extract was screened phytochemically using standard procedures.The extract was formulated into cream at concentrations 0%w/w, 2.5%w/w, 5.0%w/w, 7.5%w/w and 10.0%w/w respectively. The cream formulations were evaluated against Tricophyton tonsurans and Epidermophyton floccosum as test organisms using ketoconazole cream as reference. The extraction gave a yield of 10.68%w/w. The phytochemical screening indicated presence of saponin, tannins and alkaloids. The extract showed activity against Tryhophyton tonsurans only with mean inhibition zones of 10.00mm to 16.00mm for all the concentrations tested. Cream formulations gave favourable physical characteristics and zones of inhibition of 12.00mm and 15.00mm against Tricophyton tonsurans at 7.5%w/w and 10.0%w/w concentrations respectively. This compares favourably with ketoconazole cream with inhibition zone of 18.00mm. The results of this work show that Acalypha wilkesiana leaf extract cream has potential in treating fungal infection of the skin due to presence of Tricophyton tonsurans.